2016
DOI: 10.1007/s12011-016-0705-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Maternal Urinary Cadmium with Trimester-Specific Blood Pressure in Pregnancy: Role of Dietary Intake of Micronutrients

Abstract: Previous studies revealed associations of urinary Cd (U-Cd), a chronic Cd exposure biomarker, with blood pressure (BP) in non-pregnant adults. However, the evidence regarding trimester-specific blood pressure in pregnancy and U-Cd and effect modification by dietary intake of micronutrients is scarce. We randomly selected 653 women from the Omega Study cohort. U-Cd was quantified by inductively coupled plasma mass spectrometry. Trimester-specific, systolic (SBP) and diastolic blood pressure (DBP) were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 52 publications
1
3
0
1
Order By: Relevance
“…Assessing the BP indexes, the pregnant group showed lower systolic, diastolic and mean arterial BPs, compared to the nonpregnant control group (P<0.000). This is in consonance with a earlier similar study 24 where BP was reported to drop because of the predominantly systemic vasodilation that occurs in pregnancy, but not other studies, [25][26][27] where no significant changes in BP were observed and there may be an increase in the BP parameters. 15,28 In this regard, the study in Tokyo conducted by Jwa and colleagues, 29 stated the exception to BP fall in mid-pregnancy is only among the category of pregnant women prone to developing pregnancy induced hypertension (PIH).…”
Section: Haemodynamicssupporting
confidence: 91%
“…Assessing the BP indexes, the pregnant group showed lower systolic, diastolic and mean arterial BPs, compared to the nonpregnant control group (P<0.000). This is in consonance with a earlier similar study 24 where BP was reported to drop because of the predominantly systemic vasodilation that occurs in pregnancy, but not other studies, [25][26][27] where no significant changes in BP were observed and there may be an increase in the BP parameters. 15,28 In this regard, the study in Tokyo conducted by Jwa and colleagues, 29 stated the exception to BP fall in mid-pregnancy is only among the category of pregnant women prone to developing pregnancy induced hypertension (PIH).…”
Section: Haemodynamicssupporting
confidence: 91%
“…Inverse associations were found between urine Cd levels and hypertension in four studies ( Garner and Levallois, 2017 ; Noor et al, 2018 ; Vallee et al, 2020 ; Wu et al, 2018 ); the first of these studies found this inverse association in smokers only; and two articles ( Gao et al, 2018 ; Osorio-Yanez et al, 2016 ) found an inverse relationship between urinary Cd and blood pressure.…”
Section: Resultsmentioning
confidence: 97%
“…The studies that met the inclusion criteria were still limited compared to other heavy metal studies (Zhong, et al 2022), this con ned us from exploring deeper. Furthermore, some studies reported the correlation between Cd and preeclampsia but did not report their data completely, and hence we could not pool them together for further analysis (Kovalchuk, et al 2013;Osorio-Yañez, et al 2016).…”
Section: Discussionmentioning
confidence: 99%